2003
DOI: 10.1002/jnr.10786
|View full text |Cite
|
Sign up to set email alerts
|

Mice lacking tissue plasminogen activator and urokinase plasminogen activator genes show attenuated matrix metalloproteases activity after sciatic nerve crush

Abstract: Plasminogen activators (PAs), tissue PA (tPA) and urokinase PA (uPA), have been shown to be induced in sensory neurons after sciatic nerve crush. These findings suggested that PAs facilitate peripheral nerve regeneration by digesting adhesive cell contacts and by activation of other proteases, thereby initiating a proteolytic cascade. Both tPA and uPA activate some matrix metalloproteases (MMPs), indirectly via plasminogen activation or directly, such as the uPA activation of MMP-2. In this study, we demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 38 publications
1
22
0
Order By: Relevance
“…The substances that can activate it are numerous, for example plasmin, which plays an important role in the process of renal interstitial fibrosis [18], and it is one of the important molecules to promote pro-MMPs’ activation [19]. Another example is urokinase-type plasminogen activator (UPA), whose upregulation is associated with the development of renal interstitial fibrosis [20], and it is also known to activate the pro-MMPs [21]. …”
Section: The Regulation Of Mmp-2 and Mmp-9 Activitymentioning
confidence: 99%
“…The substances that can activate it are numerous, for example plasmin, which plays an important role in the process of renal interstitial fibrosis [18], and it is one of the important molecules to promote pro-MMPs’ activation [19]. Another example is urokinase-type plasminogen activator (UPA), whose upregulation is associated with the development of renal interstitial fibrosis [20], and it is also known to activate the pro-MMPs [21]. …”
Section: The Regulation Of Mmp-2 and Mmp-9 Activitymentioning
confidence: 99%
“…It has been reported that tPA may be an activator of MMP-9 [19]. Mice lacking tPA genes showed a attenuated MMP-9 activity after sciatic nerve crush [20]. Our study indicated that up-regulation of tPA might induce the fibrinolytic activity and the interaction of tPA and PAI regulated the fibrinolytic activity after nerve injury.…”
Section: Discussionmentioning
confidence: 66%
“…Activation of MMP2 and MMP9 is partially dependent on the presence of tissue PA (tPA) and/or urokinase PA (UPA) systems (Siconolfi and Seeds 2003) and the deletion of tPA and/or UPA interferes with functional recovery after peripheral nerve injury (Siconolfi and Seeds 2001). As with chondroitinase (Graham et al 2007;Hattori et al 2008;Udina et al 2010), the administration of exogenous MMP2 has been shown to degrade chondroitin sulphate proteoglycans and to improve recovery and anatomical reinnervation following nerve transection; furthermore, in the presence of saturating concentrations of MMP2, the co-administration of chondrotinase ABC does not produce any additional improvement, suggesting that both enzymes attack the same target (Zuo et al 1998a(Zuo et al , 1998b.…”
Section: Adhesion Moleculesmentioning
confidence: 99%